Students' Perception in applying lesson Study in Teaching Introduction to Linguistics - Trisnendri Syahrizal, Ida Lisdawati & (LPPM Universitas Advent Indonesia, 2017)
Lesson Study is an approach used in learning process. It has attracted educators, experts, and professional in the area to make use of it in proving the lesson. This study focuses on the students’ perception in applying Lesson study of teaching Introduction to Linguistics. As this case study, it will focus on Introduction to Linguistics subject. Interview and questionnaire was used to collects information on how Lesson study was normally conducted and observation was used to see the real implementation of Lesson study and during the teaching and learning process become a great attention here. Keywords: lesson study, linguistics, perception